The Effect of Familism Emotions on Post-Traumatic Growth Among the Elderly in China: The Mediating Roles of Taoist Personality and Sense of Community - Song Y; Chen Q; Wang L (Psychology Research and Behavior Management, 2024)
Yirui Song, Qianqian Chen, Lei Wang Department of Psychology, Wuhan Sports University, Wuhan, People’s Republic of ChinaCorrespondence: Lei Wang, Department of Psychology, Wuhan Sports University, No. 461 Luoyu Road, Hongshan District, Wuhan, 430079, People’s Republic of China, Email 378299706@qq.comPurpose: Post-traumatic growth is a significant social issue in the management of active aging in elderly people. This study investigates the influence of familism emotions on post-traumatic growth (PTG) of the elderly, and the mediating role of Taoist personality and sense of community (SOC) therein, to provide a scientific basis for the development of positive aging in the elderly.Methods: A cross-sectional study was conducted in several communities of Hubei Province in China. A total of 338 elderly people were investigated with the Familism Emotion Scale, PTG Scale, Taoist Personality Scale and SOC Scale. SPSS 23.0 was used to derive descriptive statistics and conduct a common method bias test, Pearson correlation analysis, and multiple stepwise regression analysis. Mplus 7.3 was used for structural equation modeling to test the significance of parallel mediation effects on the data.Results: The results show that: (1) Familism emotions, Taoist personality and SOC are positively correlated with PTG; (2) Familism emotions, Taoist personality and SOC can all positively predict PTG in the elderly; (3) Both Taoist personality and SOC partially mediated the link between familism emotions and PTG in the elderly.Conclusion: In the context of particularly constraining societal events such as COVID-19, it is necessary to pay careful attention to the impact of external environmental influences upon the elderly, such as family and community, and to encourage elderly people to cultivate a more Taoist personality. The formation of a Taoist personality offers a promising new focus for research in elderly healthcare.Keywords: familism emotions, post-traumatic growth, Taoist personality, sense of community, elderly